Students harassing students: the emotional and educational toll on kids - Cantrell, Jan (Rowman & Littlefield Education, 2008)
How big is the problem and why is it happening? -- What is sexual harassment? -- What should teachers do about peer/peer sexual harassment? -- What is the school counselor's role? -- Preventing peer/peer sexual harassment of LGBT students -- Internet issues -- Legal issues and case history -- Policy development -- What can parents and student do? -- A final word to administrators